Bibliographical resources available in the Internet about dangerous substances and residues and their influence in the environment in the period 1975-2005 Recursos bibliográficos disponibles en Internet sobre sustancias y residuos peligrosos y su influencia en el medio ambiente en el periodo 1975 a 2005 - Elena Ronda-Pérez; Verónica Juan-Quilis; Javier Sanz-Valero (Revista de Salud Ambiental, 2008)
Introduction. The Internet has become the most used source of biomedical information. The documentation, produced by the public and private institutions, in relation with the dangerous substances that can recover in the Internet is fundamental for the prevention of this type of risks. Objective. To locate and to check the available documents in the Internet about dangerous substances, dangerous residues, including inert, and his influence in the environment in the period 1975 - 2005. Material and Method. Descriptive and cross sectional study of the results of the bibliographical searches made in the Internet, in the corresponding databases. Results. It has been recognized 162 records that expire with the requirements indicated in the pre-established methodology. Discussion. With respect to the environmental documentation present in the Internet it seems to be suitable to increase his diffusion and to improve his classification and accessibility. Introducción. Internet se ha convertido en una fuente de información biomédica cada vez más utilizada. La documentación producida por las instituciones públicas y privadas, en relación con las sustancias peligrosas que se pueden recuperar en Internet, es fundamental para la prevención de este tipo de riesgos. Objetivo. Localizar y revisar los documentos disponibles en Internet sobre sustancias peligrosas, residuos peligrosos, incluyendo inertes, y su influencia en el medio ambiente en el periodo 1975 a 2005. Material y método. Estudio descriptivo transversal de los resultados de las búsquedas bibliográficas efectuadas en Internet, en las correspondientes bases de datos. Resultados. Se han reconocido 162 registros que cumplen con los requisitos señalados en la metodología preestablecida. Discusión. Con respecto a la documentación medioambiental pre- sente en Internet, parece conveniente incrementar su difusión y mejorar su clasificación y accesibilidad.